Incident photon-to-current efficiency of thermally treated SWCNTs-based nanocomposite for dye-sensitized solar cell - Mahalingam S.; Abdullah H.; Amin N.; Manap A. (Institute for Ionics, 2023)
Annealing; Electron transport properties; Energy gap; Indium compounds; Light; Nanostructured materials; Photons; Single-walled carbon nanotubes (SWCN); Sol-gel process; Sol-gels; Solar cells; Thermodynamic stability; Yarn; Annealing temperatures; Charge collection efficiency; Electron recombinations; In2O3; Incident photon-to-current efficiencies; IPCE; Morphology transitions; Single-walled carbon nanotube (SWCNTs); Dye-sensitized solar cells